Uso de moringa como bioestimulante foliar en pimiento capsicum annuum l germoplasma local en Palmales Arenillas - Romero Romero, Oscar Eduardo (2015)
There is a need to find other alternatives for managing the different cultivars that develop or have the potential our province, why the paper entitled "Using moringa as foliar biostimulant in pepper (Capsicum annuum L.) local germplasm in Palmales, Arenillas" was established for which they were established as specific objectives to assess the effect of different concentrations of extracts from the leaf of the species Moringa oleifera Lam., in the cultivation of pepper local germplasm, Read the fenométrico effect of cultivating pepper germplasm Local applying bioestimulantes based Moringa and assess the economic effect of different extracts in the pepper crop. Design of randomized complete block (RCBD) in which five treatment and four replications and experimental units give 20 as dependent variables were evaluating Days to harvest, the number, length, diameter and weight of fruit were set was used, Production: quality and quantity and the respective analysis of profitability. With the help of descriptive and inferential statistics they served to check the hypotheses, while with the help of the Tukey HDS test 95 statistical confidence homogeneous groups and contrasts between the classes analyzed. Pepper responded good to the implementation of bioestimulante product and especially the dose applied, leaving the production and profit margins.